2004
DOI: 10.1142/s0217979204018503
|View full text |Cite
|
Sign up to set email alerts
|

Transversal Magnetic Field Effect on the Populations of Excited States of Helium Atoms in Nanosecond Discharge

Abstract: Mechanism's effect of transversal magnetic field on the populations of excited states of He atoms has been investigated. Furthermore, the dependencies of complete absorption of He(I) spectral line transition 33P0,1,2–23S1 on optical plasma density are calculated by numerical methods taking into consideration the fine-structure and Zeeman splitting schemes of the spectral lines. Using the calculated values and experimental results, the dynamics of the populations of He(I) metastable states 23S1 of the He nanose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Thus, the formation time τ f of the volume discharge is restricted by the instabilities formed as occurred in a discharge column and as in the preelectrode regions [21,22]. In other papers [20,23] by some authors of this work, it has been demonstrated that at the moment of sharp breakdown voltage decrease (U 0 ) across the gap spacing after the operation of a discharge, some quasistationary potential operation is established known as the volume discharge potential operation (U VD ), which takes place for a definite time called τ VD . Moreover, their experimental results show that U VD is little dependent on the applied voltage U across the electrodes at a constant gas pressure (p).…”
Section: Dynamic Formation Of the Stage Of Volume Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the formation time τ f of the volume discharge is restricted by the instabilities formed as occurred in a discharge column and as in the preelectrode regions [21,22]. In other papers [20,23] by some authors of this work, it has been demonstrated that at the moment of sharp breakdown voltage decrease (U 0 ) across the gap spacing after the operation of a discharge, some quasistationary potential operation is established known as the volume discharge potential operation (U VD ), which takes place for a definite time called τ VD . Moreover, their experimental results show that U VD is little dependent on the applied voltage U across the electrodes at a constant gas pressure (p).…”
Section: Dynamic Formation Of the Stage Of Volume Dischargementioning
confidence: 99%
“…Taking into consideration that, at the quasi-stationary stage and constant gas pressure, U 0 = U VD + U k , and since U VD ≈ 3000 V is constant under the present experimental conditions, an increase in U 0 will lead to an increase in U k and, accordingly, to an increase in the current density j k in the cathode region [22,23]. In order to make the contribution of cathode spots to the discharge current density of the volume discharge stage clear, we use the following approach.…”
Section: Radiation Spectra and Pre-cathode Plasma Of Volume Dischargementioning
confidence: 99%